House of cards. The complete third season [videorecording (DVD)]. - Spacey, Kevin; Gill, Michel, 1960-; Wright, Robin, 1966- (Sony Pictures Home Entertainment, 2015)
A congressman works with his wife to seek revenge on those who have wronged him.